INFLUÊNCIA DO IMC NA FORÇA MUSCULAR EM ESCOLARES DO ENSINO MÉDIO - Fernando Costa Baia; Wagner Soares Nascimento; Ana Rubia Menezes Barbosa; Adriano Robson Nogueira da Lucena; Joeliton Elias Pereira; Cidia Vasconcellos; Rafael Ayres Romanholo (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
The aim of this study was to analyze the influence of the body mass index (BMI) on the muscle strength in high school students. It was used the descriptive method and the sample consisted of 38 students, with a mean age of 15.4 (± 5.0) years old for both genders. For evaluation purposes, weight and height measurements were employed to predict body mass index (BMI), according to the international table of reference (Cole and collaborators, 2000). To analyze the physical fitness, we used the following physical tests: explosive strength of upper (medicineball pitch) and lower limb strength (standing long jump), proposed by Project Sport Brazil (PROESP-BR). The results showed that (88.5%) of the sample falls in the overweight classification, with a higher prevalence in females (85.7%). It was also found that the average forces in males was higher than in females and that there was influence of BMI on the lower limb strength for females. In conclusion, it seems that there is influence of BMI on the decreased strength of the lower limbs in females, indicating that, somehow, the excess of body weight in females tends to undermine the strength of the lower limbs.